States' Performance in Reducing Uninsurance Among Black, Hispanic, and Low-Income Americans Following Implementation of the Affordable Care Act (Mary Ann Liebert, 2021)
Purpose: To assess state-level variation in changes in uninsurance among Black, Hispanic, and low-income Americans after implementation of the Affordable Care Act (ACA). Methods: We analyzed data from the Behavioral Risk Factor Surveillance System from 2012 to 2016, excluding 2014. For Black, Hispanic, and low-income (<$35,000/year) adults 18?64 years of age, we estimated multivariable regression adjusted pre- (2012?2013) to post-ACA (2015?2016) percentage point changes in uninsurance for each U.S. state. We compared absolute and relative changes and the proportion remaining uninsured post-ACA across states. We also examined whether state-level variation in coverage gains was associated with changes in forgoing needed care due to cost. Results: The range in the percentage point reduction in uninsurance varied substantially across states: 19-fold for Black (0.9?17.4), 18-fold for Hispanic (1.2?21.5), and 23-fold for low-income (1.0?27.8) adults. State-level variation in changes in uninsurance relative to baseline uninsurance rates also varied substantially. In some states, more than one quarter of Black, one half of Hispanic, and approaching one half of low-income adults remained uninsured after full implementation of the ACA. Compared with states in the lowest quintile of change in coverage, states in the highest quintile experienced greater improvements in ability to see a physician. Conclusions: Performance on reducing uninsurance for Black, Hispanic, and low-income Americans under the ACA varied substantially among U.S. states with some making substantial progress and others making little. Post-ACA uninsurance rates remained high for these populations in many states.